Un-democratic acts : new departures for dialogues in society and schools - Lowery, Charles; Walker, Anthony; Thomas, Cornell (Sense Publishers, 2016)
In Un-Democratic Acts: New Departures for Dialogues in Society and Schools, the focus is on ideals of democracy and democratic leadership to promote passionate debate, critical thinking, and change. Each chapter utilizes the unique voice and experiences of the author to tackle topics that are often taboo and/or politicized for ratings or votes but seldom for progress and change. Rather than continuing the circular course of back and forth arguments whose beginning and end points are the same, the authors utilize their voice to invoke change and focus on solutions. While each chapter takes on a life of its own, the collective work embodies the purpose and challenge that today's leadership faces from a variety of perspectives. Most importantly these concepts are intended to create dissonance and divergence, a moving away from the typical and usual ways of doing, to break down the status quo thinking that dominates the related fields of academia and schooling. Do we accept the status quo and work to find our niche within the system? Or, do we hold ourselves and others accountable to truly honor the founding principles of freedom and equality for all as professed in the United States Constitution? In Un-Democratic Acts: New Departures for Dialogues in Society and Schools, the editors create a space in which imagining the possibility of a democratic and just society where all individuals are truly respected and treated fairly is the American way.